Machining and advanced manufacturing technology X selected, peer reviewed papers from the 10th International conference on machining and advanced manufacturing technology, November 7-9 2009, Jinan, China - Yao, Yingxue; Zuo, Dunwen; Xu, Xipeng (Key engineering materials ;, 2010)
This collection of 142 papers was carefully selected from the more than 300 papers submitted. All of the papers were subjected to peer-review by at least two expert referees. The collection covers the latest theoretical and experimental research on machining and advanced manufacturing technology. It covers a remarkably wide range of topics: Theory and technology of cutting and grinding, New technologies of tool, Precision and ultra-precision machining, Advanced manufacturing processes and technology, Micro-nano technology and micro-systems, Mechanical manufacturing experiment and detection technology, Automation and modern manufacturing systems, Advanced manufacturing models and strategies. This is an up-to-date overview of the latest developments in the fields of machining and advanced manufacturing technology, and will be essential reading for anyone having an interest in this research field.